Silicon and agar on in vitro development of cockscomb (Amaranthaceae) - Assis, Franscinely Aparecida de; Souza, Genaina Aparecida de; Dias, Gabrielen de Maria Gomes; Assis, Gleice Aparecida de; Rodrigues, Filipe Almendagna; Pasqual, Moacir; Costa, Bárbara Nogueira Souza; Carvalho, Fabio Janoni (Pesquisa Agropecuaria Brasileira, 2018)
The objective of this work was to evaluate the effect of silicon and agar concentrations on cockscomb (Celosia cristata) (Amaranthaceae) development in vitro. Phytotechnical, anatomical, and ultrastructural analyses were carried out in a completely randomized design, in a 4x3 factorial arrangment, with four silicic acid concentrations (0.0, 0.5, 1.0, and 1.5 g L-1) and three agar concentrations (5.5, 8.0, and 10.5 g L-1), totaling 12 treatments with seven replicates. Celosia cristata explants were inoculated in vitro in a Murashige & Skoog (MS) culture medium, with 30 g L-1 sucrose. The analyses were conducted 30 days after inoculation. Phytotechnical traits improve with agar concentration of 8.0 g L-1, and the association of this concentration with 1.0 g L-1 silicon also contributes to the improvement of anatomical attributes, especially of leaf blade width and thickness of the palisade and spongy parenchyma, which contributes to the development of C. cristata. None of the evaluated combinations of agar and silicon contributes to Si deposition on the foliar epidermis of this ornamental species.